Method for decomposing carbon tetrafluoride
By using the synergistic aluminium isopropoxide material with a wormhole-like structure on the surface and the low-temperature plasma field, the problems of low efficiency and complex process in the prior art are solved, and high efficiency and safety are achieved decomposition effect of carbon tetrafluoride.
Patent Information
- Application Number
- CN202411415704.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-10-11
AI Technical Summary
The prior art is low in efficiency and complex in decomposition of carbon tetrafluoride, especially due to the small pore size and small number of surfactant positions of the catalyst, resulting in low decomposition efficiency, and high energy consumption and corrosive products in plasma methods. safety hazards.
Amorphous isopropoxide material with a wormhole-like structure on the surface is used as mesoporous aluminum, and carbon tetrafluoride decomposition is carried out in combination with a low-temperature plasma field. The high specific surface area of mesoporous aluminum and abundant hydroxyl active sites are used. , synergistic plasma catalysis to achieve efficient decomposition of carbon tetrafluoride.
The decomposition efficiency of carbon tetrafluoride is achieved to reach 99%, which is easy to operate, reduces energy consumption, and expands application prospects, avoiding the generation of corrosive products.
Smart Images

Figure CN119303436A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the application field of a catalyst for decomposing carbon tetrachloride, in particular to a method for decomposing carbon tetrafluoride. Background Art
[0002] Carbon tetrafluoride (CF4) is a typical strong greenhouse gas. The CF bond in the CF4 molecule has a chemical bond energy of up to 543±4 kJ / mol, which makes it extremely chemically stable and has the ability to absorb long-wave radiation. The global warming potential (GWP) of CF4 is 6,500 times that of CO2, and its lifespan in the atmosphere is as long as 50,000 years.
[0003] At present, there are many methods for CF4 decomposition, such as thermal catalysis and plasma. Due to the strong stability of CF4, it needs to be heated to 1000 degrees to achieve CF4 decomposition by heat alone. Although the introduction of catalysts can effectively reduce the decomposition temperature of CF4, the existing catalysts still need to be above 600°C to maintain efficient degradation of CF4. Low-temperature plasma is a flue gas pollution purification technology that has attracted much attention in recent years. Its advantage is that it can achieve the decomposition and purification of flue gas pollutants under normal temperature conditions. Studies have shown that plasma can effectively decompose CF4 into a variety of products by exciting the active particles produced by gas molecules. However, since plasma alone is the decomposition of CF4 achieved by energy excitation, it is inevitable that there is a problem of high energy consumption. At the same time, corrosive decomposition products such as HF F2 will also corrode the discharge equipment, posing serious safety hazards. The synergistic effect between catalysts and plasma can improve the efficiency of plasma chemical processes. The plasma discharge process will excite gas molecules to produce a large number of high-energy particles, strengthen the chemical reaction between gas and catalyst, and achieve the purpose of reducing energy consumption and improving efficiency. The aforementioned patent ZL 20221 1529433.7 reported a method for using carbon-supported alumina as a catalyst to catalyze and decompose CF4 in cooperation with low-temperature plasma. However, the catalyst has a low decomposition efficiency due to its small pore size and small number of surface active sites. The present invention provides a method for efficiently catalyzing and decomposing CF4 by combining hydroxyl-rich mesoporous aluminum with plasma. The hydroxyl-rich mesoporous aluminum has the advantages of rich surface hydroxyl groups and a well-developed pore structure, which strengthens the decomposition reaction between CF4 and the catalyst surface. Summary of the invention
[0004] The main purpose of the present invention is to provide a method for decomposing carbon tetrafluoride, aiming to solve the problem of low efficiency of decomposing carbon tetrafluoride by using the existing technology.
[0005] To achieve the above object, the present invention provides a method for decomposing carbon tetrafluoride, comprising the steps of:
[0006] The carbon tetrafluoride-containing gas to be treated flows through the mesoporous aluminum in a low-temperature plasma field for decomposition treatment;
[0007] Wherein, the oxygen concentration in the carbon tetrafluoride-containing gas is ≤10%;
[0008] The mesoporous aluminum is placed in the discharge region of the low-temperature plasma field;
[0009] The mesoporous aluminum is an amorphous aluminum isopropoxide material with a wormhole-like structure on the surface.
[0010] Furthermore, the flow rate of the carbon tetrafluoride-containing gas in the low-temperature plasma field is 10 to 50 mL / min.
[0011] Furthermore, the input voltage of the plasma reactor forming the low-temperature plasma field is 10 to 60 kV.
[0012] Furthermore, the specific surface area of the mesoporous aluminum is ≥300m 2 / g; the pore volume of the mesoporous aluminum is ≥0.5cm 3 / g; the pore size of the mesoporous aluminum is 2 to 50 nm.
[0013] Furthermore, the method for obtaining the mesoporous aluminum includes:
[0014] Mixing the polyether solution, nitric acid and aluminum isopropoxide to obtain a mixture;
[0015] The ratio of the added amount of the polyether P123, the nitric acid, and the aluminum isopropoxide is 1 g:1.5 ml:2-4 g, wherein the concentration of the nitric acid is 65%;
[0016] The mixture is sequentially subjected to stirring treatment, drying treatment and calcination treatment to obtain mesoporous aluminum;
[0017] Wherein, the calcination temperature is 600-800°C.
[0018] Furthermore, the polyether solution is obtained by dissolving 1 g of polyether P123 in 20 mL of ethanol to obtain the polyether solution.
[0019] Furthermore, the stirring treatment is performed for 4 to 8 hours.
[0020] Furthermore, the temperature of the drying treatment is 50-80° C.; and the duration of the drying treatment is 2-4 days.
[0021] Furthermore, the calcination treatment lasts for 3 to 8 hours.
[0022] Furthermore, the heating rate of the calcination treatment is 2°C / min.
[0023] The beneficial effects achieved by the present invention are:
[0024] The method for decomposing carbon tetrafluoride provided by the present invention is to decompose carbon tetrafluoride gas (oxygen content ≤ 10%) to be treated by passing through mesoporous aluminum (amorphous aluminum isopropoxide material with wormhole-like structure on the surface) in the discharge area of the low-temperature plasma field in a low-temperature plasma field. The decomposition efficiency of carbon tetrafluoride can reach 99% by using this method for decomposing carbon tetrafluoride; the operation is simple and the application prospect is broad. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.
[0026] Figure 1 The effect of mesoporous aluminum synthesized under different aluminum sources on the decomposition efficiency of CF4 in Example 2 of the present invention;
[0027] Figure 2 The effect of mesoporous aluminum synthesized at different calcination temperatures on the decomposition efficiency of CF4 in Example 3 of the present invention;
[0028] Figure 3 The comparison of the decomposition efficiency of CF4 by mesoporous aluminum and commercial Al2O3 coupled plasma in Example 4 of the present invention;
[0029] Figure 4 The comparison of the decomposition efficiency of CF4 by mesoporous aluminum coupled plasma at different flow rates in Example 5 of the present invention;
[0030] Figure 5 The comparison of the decomposition efficiency of CF4 with plasma at different flow rates in Example 6 of the present invention;
[0031] Figure 6 Schematic diagram of the effect of oxygen-containing flue gas on CF4 decomposition performance in Example 7 of the present invention;
[0032] Figure 7 (a) is a SEM image of the mesoporous aluminum before reaction in Example 8 of the present invention; Figure 7 (b) is a SEM image of the mesoporous aluminum after reaction in Example 8 of the present invention;
[0033] Figure 8 This is the full XPS spectrum of mesoporous aluminum before and after the reaction in Example 9 of the present invention;
[0034] Fig. 9The mesoporous aluminum NH3-TPD before and after the reaction in Example 10 of the present invention;
[0035] Fig.10 The mesoporous aluminum in Example 10 of the present invention and the commercial Al2O3 NH3-TPD;
[0036] Fig.11 (a) is the infrared absorption of pyridine before the mesoporous aluminum reaction in Example 11 of the present invention; Fig.11 (b) is an infrared image of pyridine adsorption after the mesoporous aluminum reacted in Example 11 of the present invention;
[0037] Fig.12 (a) is mesoporous aluminum in Example 12 of the present invention and commercial Al2O3CO2-TPD; Fig.12 (b) is the mesoporous aluminum CO2-TPD before and after the reaction in Example 11 of the present invention;
[0038] Fig.13 (a) is the Al 2p XPS spectrum of mesoporous aluminum in Example 13 of the present invention, Fig.13 (b) is the C1s XPS spectrum of mesoporous aluminum in Example 13 of the present invention; Fig.13 (c) is the O1s XPS spectrum of the mesoporous aluminum in Example 13 of the present invention; Fig.13 (d) is the F1s XPS spectrum of the mesoporous aluminum in Example 13 of the present invention;
[0039] Fig.14 (a) is a SEM image of the mesoporous aluminum in Example 9 of the present invention; Fig.14 (b) is the XRD diffraction pattern of the mesoporous aluminum in Example 9 of the present invention; Fig.14 (c) is a TEM image of the mesoporous aluminum in Example 9 of the present invention; Fig.14 (d) is the selected area electron diffraction of the mesoporous aluminum in Example 9 of the present invention;
[0040] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with the implementation methods and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0041] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0042] It should be noted that, in the absence of conflict, the following embodiments and features in the embodiments can be combined with each other. It should also be understood that the terms used in the embodiments of the present invention are intended to describe specific embodiments rather than to limit the scope of protection of the present invention.
[0043] Unless otherwise defined, all technical and scientific terms used in the present invention are consistent with the prior art mastery of the technicians in this technical field and the records of the present invention. Any methods, equipment and materials of the prior art similar to or equivalent to the methods, equipment and materials in the embodiments of the present invention can also be used to implement the present invention. It should be known by those skilled in the art that, as an explanation of the present application document, without affecting the actual understanding of the technical solution of the present application, "Intensity (au)" can be expressed as intensity, "Stress" can be expressed as stress, "Strain" can be expressed as strain, "Grain size" can be expressed as grain size, and "Frequency" can be expressed as frequency.
[0044] When the embodiments give numerical ranges, it should be understood that unless otherwise specified in the present invention, both endpoints of each numerical range and any value between the two endpoints can be selected. The test methods in the following embodiments without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturers. The materials or reagents required in the following embodiments are commercially available unless otherwise specified.
[0045] In order to solve the problems of low efficiency and complicated process of decomposing carbon tetrafluoride by using the prior art, the present invention provides a method for decomposing carbon tetrafluoride, comprising the steps of:
[0046] The carbon tetrafluoride-containing gas to be treated flows through the mesoporous aluminum in a low-temperature plasma field for decomposition treatment.
[0047] Among them, the oxygen concentration in the carbon tetrafluoride-containing gas is ≤10%. It was found during the experiment that oxygen itself will decompose in the plasma field and consume the energy of the plasma field, thereby forming a competitive relationship with the decomposition of CF4. Under oxygen-free conditions, the decomposition efficiency of CF4 by mesoporous aluminum coupled plasma is the highest. After the introduction of O2, the highest CF4 decomposition efficiency is greatly reduced, and the oxygen concentration in the carbon tetrafluoride-containing gas should not exceed 10%. Since O2 has electronegativity, when the O2 in the reaction system reaches a certain concentration, it will compete with CF4, reducing the energy of the plasma acting on CF4, resulting in a decrease in the decomposition efficiency of CF4 by the plasma. In addition, the O2 introduced under the action of plasma will react with mesoporous aluminum, change the surface active sites of mesoporous aluminum, and cause the decomposition efficiency of CF4 by mesoporous aluminum to decrease. Preferably, there is a certain amount of oxygen in the carbon tetrafluoride-containing gas and the oxygen concentration does not exceed 10%, which helps to reduce the deposition of C transformed after CF4 decomposition on the surface of mesoporous aluminum, resulting in pore blockage of mesoporous aluminum, promoting the oxidation conversion of byproducts CH2F2 and CO, and producing more CO2.
[0048] The mesoporous aluminum is placed in the discharge region of a low-temperature plasma field.
[0049] Mesoporous aluminum is an amorphous aluminum isopropoxide material with a wormhole-like structure on the surface. Specifically, mesoporous aluminum is prepared by a sol-gel method. Experimental studies have found that the surface of mesoporous aluminum prepared by aluminum isopropoxide contains more hydroxyls, that is, the form of Al on the surface of mesoporous aluminum before the reaction is mainly Al-OH. Under the action of -OH, the F after CF4 decomposition combines with Al to form AlF3, and the C after CF4 decomposition is deposited on the surface of mesoporous aluminum and combines with the O site to form CO.
[0050] The mesoporous aluminum surface also contains a higher content of strongly acidic sites, more weakly basic sites (Al-OH) and fewer strongly basic sites (O 2- and other active oxygen), and has higher CF4 catalytic activity; among them, through experimental measurement, the strong acid sites in the mesoporous aluminum are mainly Lewis acid (L acid) and Bronsted acid (B acid), and the content of B acid sites on the surface of the mesoporous aluminum accounts for more than 50% of the total strong acid sites, indicating that it is an important active site for the CF4 decomposition reaction; at the same time, during the decomposition process, the weak alkaline sites on the surface of the mesoporous aluminum disappear and the strong alkaline sites increase, which cooperate with each other to promote the decomposition of CF4.
[0051] Compared with the mesoporous aluminum prepared by aluminum acetate and aluminum nitrate, it has a larger surface area and a more developed pore structure, which can significantly slow down the adverse effects of C and F deposition on the surface of mesoporous aluminum during the decomposition of carbon tetrafluoride, thereby significantly improving the decomposition efficiency and service life of CF4 under the same conditions.
[0052] The method for decomposing carbon tetrafluoride provided by the present invention is to decompose carbon tetrafluoride gas (oxygen content ≤ 10%) to be treated by passing through mesoporous aluminum (amorphous aluminum isopropoxide material with wormhole-like structure on the surface) in the discharge area of the low-temperature plasma field in a low-temperature plasma field. The decomposition efficiency of carbon tetrafluoride can reach 99% by using this method for decomposing carbon tetrafluoride; the operation is simple and the application prospect is broad.
[0053] Furthermore, the flow rate of the carbon tetrafluoride-containing gas in the low-temperature plasma field is 10 to 50 mL / min. Specifically, when the flow rate of the carbon tetrafluoride-containing gas in the low-temperature plasma field is 10 to 50 mL / min, the decomposition efficiency of carbon tetrafluoride can be stabilized at 70% or above. During the decomposition process, the flow rate of the carbon tetrafluoride-containing gas is not easy to be too large; first, after the flue gas flow rate increases, the amount of CF4 to be decomposed by the mesoporous aluminum per unit time will increase significantly. Therefore, under the condition of large flue gas flow rate in the same time, more C and F will be covered and deposited on the surface of the mesoporous aluminum. In addition, the energy of the plasma field under large flow will be consumed by more CF4 molecules, thereby reducing the activation energy obtained by a single CF4 molecule and reducing the decomposition efficiency.
[0054] Furthermore, the input voltage of the plasma reactor for forming the low-temperature plasma field is 10 to 60 kV.
[0055] Exemplarily, the input voltage of the plasma reactor for forming the low-temperature plasma field may be 20-40 kV.
[0056] Furthermore, the specific surface area of mesoporous aluminum is ≥300m 2 / g; the pore volume of mesoporous aluminum is ≥0.5cm 3 / g; the pore size of mesoporous aluminum is 2 to 50 nm.
[0057] Furthermore, the method of obtaining mesoporous aluminum includes:
[0058] The polyether solution, nitric acid and aluminum isopropoxide are mixed to obtain a mixture.
[0059] The mixture is sequentially subjected to stirring treatment, drying treatment and calcination treatment to obtain mesoporous aluminum.
[0060] The calcination temperature is 600-800°C.
[0061] Furthermore, the polyether solution is obtained by dissolving 1 g of polyether P123 in 20 mL of ethanol to obtain the polyether solution.
[0062] Furthermore, the stirring treatment time is 4 to 8 hours.
[0063] Furthermore, the temperature of the drying treatment is 50-80° C.; and the duration of the drying treatment is 2-4 days.
[0064] Furthermore, the calcination treatment time is 3 to 8 hours.
[0065] Furthermore, the heating rate of the calcination treatment is 2°C / min.
[0066] For further understanding of the present invention, examples are given below:
[0067] Example 1
[0068] Preparation of mesoporous aluminum
[0069] Dissolve 1 g of polyether P123 in 20 mL of ethanol at room temperature, add 1.5 mL of 65% nitric acid and 2.04 g (10 mmol) of aluminum isopropoxide while stirring the solution. Cover the mixture with plastic wrap, stir at room temperature for about 6 hours, and then heat it in a drying oven at 60°C for 2 days to evaporate the solution. Finally, calcine the obtained solid particles at 600°C for 5 hours at a heating rate of 2°C / min to obtain mesoporous aluminum.
[0070] In addition, aluminum acetate and aluminum nitrate were used as aluminum sources, respectively, and the same method was used to prepare aluminum acetate mesoporous aluminum and aluminum nitrate mesoporous aluminum, so as to compare the catalytic effects of mesoporous aluminum with different aluminum sources.
[0071] Example 2
[0072] The three mesoporous aluminum materials prepared in Example 1, namely, mesoporous aluminum (shown as aluminum isopropoxide), mesoporous aluminum aluminum acetate (shown as aluminum nitrate), and mesoporous aluminum aluminum nitrate (shown as aluminum nitrate), were decomposed under the condition of flue gas (containing carbon tetrafluoride gas) flow rate of 20 mL / min. Specifically, the decomposition process did not involve the low-temperature plasma field, and only the flue gas flowed through the three mesoporous aluminum materials at a flow rate of 20 mL / min. The decomposition efficiency was as follows: Figure 1 shown.
[0073] from Figure 1 It can be seen that the decomposition efficiency of mesoporous aluminum on CF4 is as high as 82%, which is 25% higher than that of mesoporous aluminum acetate, while the decomposition efficiency of mesoporous aluminum nitrate on CF4 is only 38%. This indicates that the more hydroxyl groups on the surface of mesoporous aluminum may play a role in making it more efficient in decomposing CF4.
[0074] Example 3
[0075] Compared with the mesoporous aluminum preparation process in Example 1, the calcination temperature was changed to 300°C and 800°C, respectively, to obtain mesoporous aluminum-300°C (300°C in the figure) and mesoporous aluminum-800°C (800°C in the figure).
[0076] The carbon tetrafluoride-containing gas was flowed through mesoporous aluminum-300°C (300°C in the figure), mesoporous aluminum-800°C (800°C in the figure), and mesoporous aluminum prepared in Example 1 (600°C in the figure) at a flow rate of 20 mL / min to decompose CF4. The specific decomposition efficiency is as follows: Figure 2 shown.
[0077] from Figure 2 It can be seen that when the calcination temperature is 300°C, the decomposition efficiency of mesoporous aluminum to CF4 is low, at 57%; when the calcination temperature is increased to 600°C, the decomposition efficiency of mesoporous aluminum to CF4 increases to 82%; when the calcination temperature is further increased to 800°C, the decomposition efficiency of mesoporous aluminum to CF4 has no obvious change, and is still at a high decomposition efficiency. Therefore, the optimal calcination temperature of the mesoporous aluminum of the present invention is 600°C.
[0078] Example 4
[0079] The mesoporous aluminum prepared in Example 1, commercial Al2O3, and non-catalytic material (blank control group; the figure shows single plasma) were respectively coupled to a plasma reactor with an input voltage of 25V to carry out a comparative experiment on the decomposition of carbon tetrafluoride.
[0080] That is, a 10% carbon tetrafluoride gas was flowed at a flow rate of 10 mL / min through the mesoporous aluminum (shown as mesoporous aluminum), commercial Al2O3 (shown as commercial Al2O3), and a catalytic material (blank control group; shown as plasma alone) prepared in Example 1, which were all in a low-temperature plasma field formed by a plasma reactor with an input voltage of 25 V, to perform carbon tetrafluoride decomposition treatment, and the decomposition efficiency of the treatment from 0 to 600 min was recorded, as shown in detail. Figure 3 shown.
[0081] according to Figure 3 As shown in the figure, the decomposition efficiency of CF4 by mesoporous aluminum rapidly increased to 85% within the initial 200 minutes, and then slowly increased to a peak of about 99% after about 400 minutes. Under the same conditions, the peak decomposition efficiency of commercial Al2O3 for CF4 was only 74%, and the decomposition efficiency dropped to below 50% at 300 minutes, which was equivalent to the decomposition efficiency of CF4 by plasma alone, indicating that the commercial Al2O3 had been deactivated at this time.
[0082] Example 5
[0083] The carbon tetrafluoride-containing gas with flue gas flow rates of 10 mL / min, 20 mL / min, and 50 mL / min was respectively passed through the mesoporous aluminum prepared in Example 1 in a low-temperature plasma field formed by a plasma reactor with an input voltage of 25 V (shown in the figure as 10 mL / min, 20 mL / min, and 50 mL / min, respectively), and the carbon tetrafluoride decomposition treatment was performed, and the decomposition efficiency of the treatment from 0 to 400 min was recorded, as shown in detail. Figure 4 shown.
[0084] from Figure 4 It can be seen that when the flue gas flow rate is 10mL / min, the decomposition efficiency of CF4 by mesoporous aluminum can reach up to 99%. When the flue gas flow rate is increased to 20mL / min, the maximum decomposition efficiency of CF4 by mesoporous aluminum is reduced to 82%, and when the flue gas flow rate is further increased to 50mL / min, the decomposition efficiency is reduced to 70%. The experimental results show that the decomposition efficiency of CF4 decreases with the increase of flue gas flow rate.
[0085] This indicates that as the flue gas flow rate increases, the amount of CF4 that the catalyst needs to decompose per unit time will increase significantly. Therefore, under the condition of large flue gas flow rate in the same time, more C and F will be covered and deposited on the catalyst surface.
[0086] The mesoporous aluminum prepared at a calcination temperature of 600°C with aluminum isopropoxide as the aluminum source has the best catalytic effect. The maximum decomposition efficiency of CF4 by mesoporous aluminum coupled plasma can reach 99%, which is 25% higher than that of commercial Al2O3 aluminum. After increasing the flow rate, the energy of the plasma field will be consumed by more CF4 molecules, thereby reducing the activation energy obtained by a single CF4 molecule and reducing the decomposition efficiency.
[0087] Example 6
[0088] Compared with Example 5, no mesoporous aluminum is provided in the low-temperature plasma field. That is, the carbon tetrafluoride-containing gas with flue gas flow rates of 10 mL / min, 20 mL / min, and 50 mL / min respectively flows through the low-temperature plasma field formed by the plasma reactor at an input voltage of 25 V (shown as 10% CF410 mL / min, 10% CF420 mL / min, and 10% CF450 mL / min, respectively), and the carbon tetrafluoride is decomposed, and the decomposition efficiency of the treatment from 0 to 150 min is recorded, as shown in detail. Figure 5 shown.
[0089] from Figure 5 It can be seen that the decomposition efficiency of CF4 under the action of plasma alone also decreases with the increase of flue gas flow rate. When the flue gas flow rate is 10mL / min, the decomposition efficiency of CF4 is stable at about 50%; when the flue gas flow rate is increased to 50mL / min, the stable decomposition efficiency of CF4 is reduced to about 30%.
[0090] Combination Figure 4 and Figure 5 The reason is that when the flue gas flow rate increases, the amount of CF4 to be decomposed by mesoporous aluminum per unit time will increase significantly. Therefore, under the condition of large flue gas flow rate in the same time, more C and F will be covered and deposited on the surface of mesoporous aluminum. In addition, the energy of the plasma field under large flow rate will be consumed by more CF4 molecules, thereby reducing the activation energy obtained by a single CF4 molecule and reducing the decomposition efficiency.
[0091] Example 7
[0092] Under the conditions of O2 concentration of 10% and flue gas flow rate of 20mL / min, the effect of O2 on the decomposition efficiency of CF4 was studied. Figure 6 As shown. Under oxygen-free conditions, a flue gas containing carbon tetrafluoride with a flow rate of 20 mL / min flows through a low-temperature plasma field formed by a plasma reactor with an input voltage of 25 V. The decomposition efficiency of CF4 by plasma alone is 38%. After the introduction of O2 with a concentration of 10%, the decomposition efficiency of CF4 drops to 34%, indicating that oxygen itself will decompose in the plasma field and consume the energy of the plasma field, thereby forming a competitive relationship with the decomposition of CF4.
[0093] Under anaerobic conditions, the mesoporous aluminum prepared in Example 1, in which a flue gas flow rate of 20 mL / min of carbon tetrafluoride gas flows through a low-temperature plasma field formed by a plasma reactor with an input voltage of 25 V, has a maximum decomposition efficiency of 82% for CF4. After the introduction of O2 with a concentration of 10%, the maximum CF4 decomposition efficiency drops to 65%. Since O2 has electronegativity, when the O2 in the reaction system reaches a certain concentration, it will compete with CF4, reducing the energy of the plasma acting on CF4, resulting in a decrease in the decomposition efficiency of CF4 by the plasma. In addition, the O2 introduced under the action of plasma will react with the mesoporous aluminum, change the surface active sites of the mesoporous aluminum, and cause the mesoporous aluminum to have a decreased decomposition efficiency of CF4.
[0094] Example 8
[0095] The morphology of the mesoporous aluminum before and after the reaction was analyzed by SEM in Example 7 under the conditions of an oxygen concentration of 10% and a flue gas flow rate of 20 ml / min. Figure 7 As shown, Figure 7 (a) is the SEM image of mesoporous aluminum before reaction. Figure 7 (b) is the SEM image of mesoporous aluminum after the reaction. It can be seen that there is an obvious pore structure on the surface of mesoporous aluminum before the reaction, but the pore structure on the surface of mesoporous aluminum disappears after the reaction, forming a dense layer, indicating that the CF4 decomposition reaction has a significant effect on the morphology of mesoporous aluminum. CF4 decomposition will produce C and F deposited on the surface of mesoporous aluminum, resulting in pore blockage. At the same time, F may also cause corrosion to the surface of mesoporous aluminum, thereby changing the morphology of mesoporous aluminum.
[0096] Example 9
[0097] SEM was used to analyze the changes in the surface element composition of the mesoporous aluminum before and after the reaction under the conditions of an oxygen concentration of 10% and a flue gas flow rate of 20 ml / min in Example 7. Figure 8 As shown in Figure 2, it can be seen that before the reaction, the mesoporous aluminum has characteristic peaks belonging to Al 2p and O1s at 76.51eV and 533.14eV, respectively. After the reaction, the intensity of the characteristic peak of O1s of the mesoporous aluminum is significantly weakened, and a characteristic peak belonging to F1s appears at 687.08eV.
[0098] After the CF4 decomposition reaction, the content of Al and O elements on the surface of mesoporous aluminum decreased by 8.8% and 29.1% respectively, indicating that both may have participated in the decomposition reaction of CF4. The carbon content on the surface of mesoporous aluminum was 20.66% before the reaction, and it increased significantly to 50.29% after the reaction, and the percentage of F element was as high as 10.07%.
[0099] The results confirmed that the decomposition of CF4 would produce a large amount of C and F elements deposited on the surface of mesoporous aluminum, which may be an important reason for the disappearance of the pore structure.
[0100] Table 1 shows the changes in the surface element content of mesoporous aluminum before and after the reaction.
[0101] Table 1 Comparison of element contents before and after mesoporous aluminum reaction
[0102]
[0103] Example 10
[0104] The surface element composition changes of the mesoporous aluminum before and after the reaction were analyzed by NH3-TPD in Example 7 under the conditions of an oxygen concentration of 10% and a flue gas flow rate of 20 ml / min. Fig. 9 As shown. It can be seen that before the reaction, the mesoporous aluminum has a characteristic peak at 300-500℃, corresponding to the strong acid site, with a content of 1.79mmol / g. After the reaction, the content of the strong acid site on the surface of the mesoporous aluminum dropped to 1.11mmol / g, and a new characteristic peak belonging to the weak acid site appeared at 100℃, with a content of 0.35mmol / g. The results show that the strong acid site is involved in the CF4 decomposition reaction.
[0105] This example also carried out NH3-TPD test on the commercial alumina in Example 4, as shown in FIG. Fig.10As shown in the figure, compared with mesoporous aluminum, the desorption peak of NH3 on commercial alumina during the NH3-TPD test appears at a higher temperature, and the content of strong acid sites is 1.54mmol / g, which is much lower than that of mesoporous aluminum. The mesoporous aluminum surface contains a higher content of strong acid, thus showing higher CF4 catalytic activity.
[0106] Embodiment 11
[0107] To explore the effect of the type of acidic sites on the surface of mesoporous aluminum on the decomposition of CF4, pyridine infrared (Py-FTIR) was used to analyze the mesoporous aluminum before and after the reaction in Example 7 under the conditions of an oxygen concentration of 10% and a flue gas flow rate of 20 ml / min. Fig.11 As shown, Fig.11 (a) is the pyridine adsorption before the infrared mesoporous aluminum reaction. Fig.11 (b) is the infrared mesoporous aluminum after pyridine adsorption reaction. The acid sites on the surface of mesoporous aluminum can be divided into Lewis acid (L acid) and Bronsted acid (B acid), among which the substance that can accept electron pairs is L acid, and the substance that can provide protons is B acid.
[0108] Firstly, the types and contents of acid sites of mesoporous aluminum were analyzed at 150℃, 200℃ and 350℃. The Py-FTIR spectrum showed six obvious characteristic peaks, located at 1450cm -1 、1490cm -1 、1540cm -1 、1577cm -1 、1594cm -1 and 1612cm -1 . Located at 1440-1460cm -1 The characteristic peak between the two corresponds to L acid, located at 1490 cm -1 The characteristic peaks at 1530-1550cm correspond to L acid and B acid. -1 The characteristic peaks between the two correspond to B acid, located at 1577-1620 cm -1 The characteristic peaks between correspond to L acid.
[0109] The contents of L acid and B acid are shown in Table 2, where the acid content measured at 150°C is the total acid content, and the acid content at 350°C is the strong acid content.
[0110] The results show that the content of B acid sites on the surface of mesoporous aluminum accounts for more than 50% of the total amount of strong acid sites, indicating that it is an important active site for the CF4 decomposition reaction. Before the reaction, the L acid content on the surface of mesoporous aluminum was 123.78μmol / g, and the B acid content was 56.42μmol / g. After the reaction, the L acid content increased to 243.21μmol / g, while the B acid content decreased to 3.75μmol / g, further indicating that the B acid site is an important active site participating in the CF4 reaction.
[0111] Table 2 Contents of L acid and B acid of mesoporous aluminum before and after reaction
[0112]
[0113]
[0114] Example 12
[0115] CO2-TPD was used to analyze the changes in the surface alkaline sites of the mesoporous aluminum before and after the reaction under the conditions of an oxygen concentration of 10% and a flue gas flow rate of 20 ml / min in Example 7. Fig.12 As shown, Fig.12 (a) CO2-TPD test graph of mesoporous aluminum and commercial Al2O3; Fig.12 (b) is the CO2-TPD test graph before and after the mesoporous aluminum reaction.
[0116] Mesoporous aluminum has CO2 desorption peaks at 100℃ and 400℃, corresponding to weak basic sites and strong basic sites, respectively. The content of weak basic sites is 0.85mmol / g, while the content of strong basic sites is 0.5mmol / g. After the reaction, the weak basic sites of mesoporous aluminum disappear, and the content of strong basic sites increases from 0.5mmol / g to 1.76mmol / g, indicating that the weak basic sites on the surface of mesoporous aluminum participate in the CF4 decomposition reaction. There are also weak basic sites and strong basic sites on the surface of commercial Al2O3, with contents of 0.39mmol / g and 1.32mmol / g, respectively. The weak basic content is 0.46mmol / g lower than that of mesoporous aluminum, while the strong basic content is 0.82mmol / g higher than that of mesoporous aluminum. Obviously, the more weak basic sites and fewer strong basic sites on the surface of mesoporous aluminum make it have far superior CF4 decomposition performance than commercial Al2O3.
[0117] The acid sites on the surface of alumina are usually Al 3+ and Al-OH, where Al 3+ is L acid, Al-OH is B acid; at the same time, there are usually two basic sites, namely hydroxyl ion site (Al-OH) and oxygen ion site (O 2- ), O 2- The basicity of Al-OH is stronger than that of Al-OH. Therefore, the weak basic site of the mesoporous aluminum surface is Al-OH, while the strong basic site is O 2- Al-OH can play the dual role of acidic and alkaline sites. When the reaction process only gives H + The analysis results of acid and base sites show that the surface of mesoporous aluminum contains higher hydroxyl and weakly basic sites, among which aluminum hydroxyl is a basic site and may give protons during the CF4 decomposition reaction, playing the dual role of basic site and B acid.
[0118] Embodiment 13
[0119] CO2-TPD was used to analyze the changes in the surface alkaline sites of the mesoporous aluminum before and after the reaction under the conditions of an oxygen concentration of 10% and a flue gas flow rate of 20 ml / min in Example 7. Fig.13 As shown, Fig.13 (a) is the 2p orbital electron energy spectrum of aluminum element; Fig.13 (b) 1s orbital electron energy spectrum of carbon; Fig.13 (c) 1s orbital electron energy spectrum of carbon Fig.13 (d) 1s orbital electron energy spectrum of fluorine.
[0120] The main peak of Al 2p orbital before the reaction is located at 74.17eV, and after the reaction it moves to 76.25eV. The movement of Al 2p characteristic peak to the high binding energy region indicates that Al participates in the CF4 decomposition reaction, and the charge density decreases during the reaction. Before the reaction, the morphology of Al on the surface of mesoporous aluminum is mainly Al-OH, and after the reaction it is converted into AlF3. Fig.13 As shown in (b), the characteristic peak of F1s on the surface of mesoporous aluminum after the reaction is located at 686.67 eV, corresponding to AlF3, which further indicates that the F after CF4 decomposition combines with Al to form AlF3. Fig.13 As shown in (c), the characteristic peaks at 530.77 eV and 531.89 eV before the reaction correspond to O ads After the reaction, O1s moved to a higher binding energy and a characteristic peak belonging to CO appeared at 534.73 eV, accounting for 8.38%. The -OH content decreased to 41.65%, and O ads The content ratio increased to 50.03%. This indicates that -OH participated in the decomposition of CF4 and converted it into CO. Before the reaction, C1s had three characteristic peaks at 284.71eV, 285.54eV, and 289.29eV, corresponding to CC, CO, and OC=O, respectively. Fig.13 (d) After the reaction, the CO content increased from 27.3% to 49.1%, indicating that the C from CF4 decomposition will be deposited on the catalyst surface and combine with the O site to form CO.
[0121] Among them, the XPS bond valence content analysis is shown in Table 3.
[0122] Table 3 XPS bond valence content analysis
[0123]
[0124] The content of acidic and basic sites on the surface of mesoporous aluminum is higher. Among them, the weak alkaline site is Al-OH, and the strong alkaline site is O 2-After the reaction, the Al-OH on the surface of mesoporous aluminum participates in the decomposition of CF4, transforms into C and AlF3 and deposits on the catalyst surface, resulting in pore blockage and decreased CF4 decomposition efficiency. After O2 is introduced, the oxidation conversion of byproducts CH2F2 and CO is promoted, producing more CO2.
[0125] Embodiment 14
[0126] The morphology of the mesoporous aluminum prepared in Example 1 was studied by SEM. Fig.14 As shown. There are clear macropores on the surface of mesoporous aluminum, which further shows that mesoporous aluminum is a porous material. The phase structure of mesoporous aluminum was analyzed by XRD, as shown in Fig.14 (b) There is no obvious characteristic peak in the XRD spectrum of mesoporous aluminum, indicating that the material is in an amorphous state. Fig.14 (c) is the TEM image of mesoporous aluminum, showing that the mesoporous aluminum presents a typical wormhole-like structure and there are no obvious diffraction rings in the material ( Fig.14 (d)), proving that the mesoporous aluminum is in an amorphous state and contains rich pore structures.
[0127] Table 4 Comparison of specific surface area, pore volume and pore size of catalysts
[0128]
[0129] In summary, the above technical solutions of the present invention are only preferred embodiments of the present invention, and the patent scope of the present invention is not limited thereto. All equivalent structural changes made by using the contents of the present invention specification and drawings under the technical concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.
Claims
1. A method for decomposing carbon tetrafluoride, characterized in that: Includes steps: The carbon tetrafluoride-containing gas to be treated flows through the mesoporous aluminum in a low-temperature plasma field for decomposition treatment; Wherein, the oxygen concentration in the carbon tetrafluoride-containing gas is ≤10%; The mesoporous aluminum is placed in the discharge region of the low-temperature plasma field; The mesoporous aluminum is an amorphous aluminum isopropoxide material with a wormhole-like structure on the surface.
2. The method for decomposing carbon tetrafluoride according to claim 1, characterized in that: The flow rate of the carbon tetrafluoride-containing gas in the low-temperature plasma field is 10 to 50 mL / min.
3. The method for decomposing carbon tetrafluoride according to claim 1, characterized in that: The input voltage of the plasma reactor for forming the low-temperature plasma field is 10-60V.
4. The method for decomposing carbon tetrafluoride according to claim 1, characterized in that: The specific surface area of the mesoporous aluminum is ≥300m 2 / g; the pore volume of the mesoporous aluminum is ≥0.5cm 3 / g; the pore size of the mesoporous aluminum is 2 to 50 nm.
5. The method for decomposing carbon tetrafluoride according to any one of claims 1 to 4, characterized in that: The method for obtaining the mesoporous aluminum includes: Mixing polyether P123, nitric acid and aluminum isopropoxide to obtain a mixture; The ratio of the added amount of the polyether P123, the nitric acid, and the aluminum isopropoxide is 1 g:1.5 ml:2-4 g, wherein the concentration of the nitric acid is 65%; The mixture is sequentially subjected to stirring treatment, drying treatment and calcination treatment to obtain mesoporous aluminum; Wherein, the calcination temperature is 600-800°C.
6. The method for decomposing carbon tetrafluoride according to claim 5, characterized in that: The polyether solution is obtained by dissolving 1 g of polyether P123 in 20 mL of ethanol to obtain the polyether solution.
7. The method for decomposing carbon tetrafluoride according to claim 5, characterized in that: The stirring treatment lasts for 4 to 8 hours.
8. The method for decomposing carbon tetrafluoride according to claim 5, characterized in that: The temperature of the drying treatment is 50-80° C.; the duration of the drying treatment is 2-4 days.
9. The method for decomposing carbon tetrafluoride according to claim 5, characterized in that: The calcination treatment lasts for 3 to 8 hours.
10. The method for decomposing carbon tetrafluoride according to claim 5, characterized in that: The heating rate of the calcination treatment is 2°C / min.
Citation Information
Patent Citations
Carbon-based supported aluminum oxide, preparation method thereof and application of carbon-based supported aluminum oxide in degrading CF4
CN115970670A
Core-shell-shaped alumina microsphere catalyst, preparation method thereof and application of core-shell-shaped alumina microsphere catalyst in catalytic decomposition of CF4
CN118162122A
Catalyst and method for decomposition of perfluoro-compound in waste gas
CN1681587A
Perfluorocarbon gas enriching method
JP2007319811A
Plasma-catalyst type scrubber
KR101688611B1